Laser shock peening for microstructure tailoring of additive manufactured maraging steel parts - Lee, Louis Tian Fu (Nanyang Technological University, 2020)
Additive manufacturing (AM) has been gaining popularity in the manufacturing industry with the advantages it brings about compared to traditional manufacturing techniques, allowing manufacturers to be more efficient and save money. One of the commonly used AM techniques is selective laser melting (SLM) which allows printing of parts with complex geometries. In this project, the material of focus is Maraging Steel 300 which is widely used in aviation industry to make rocket motor cases and landing gears due to its mechanical properties of having high tensile strength and high fracture toughness. Maraging steel will undergo laser shock peening (LSP) and heat treatment processes to observe the effects it has on the microstructure which will be seen under Scanning Electron Microscope (SEM). Further analysis will be studied to find out about its properties.